Low Incidence and Mortality by SARS-CoV-2 Infection Among Healthcare Workers in a Health National Center in Mexico: Successful Establishment of an Occupational Medicine Program - Salazar, Miguel Ángel; Chavez-Galan, Leslie; Castorena-Maldonado, Armando; Mateo-Alonso, Maribel; Diaz-Vazquez, Nadia Otilia; Vega-Martínez, Ana María; Martínez-Orozco, José Arturo; Becerril-Vargas, Eduardo; Sosa-Gómez, Fernando Manuel; Patiño-Gallegos, Hilda; Alonso-Martínez, Delfino; López-Segundo, Enrique; et al. (Frontiers in Public Health, 2021)
Background: COVID-19 is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Healthcare workers (HCWs) constitute a population which is significantly affected worldwide. In Mexico, the Instituto Nacional de Enfermedades Respiratorias (INER) is the principal national reference of respiratory diseases. Aim: To evaluate the efficiency of the INER-POL-TRAB-COVID19 program to mitigate the SARS-CoV-2 infection risk among the INER-healthcare workers (INER-HCW). Methods: Currently, the INER has 250 beds and 200 respiratory ventilators to support COVID-19 patients in critical condition. On March 1st, 2020, the INER-POL-TRAB-COVID19 program was launched to mitigate the SARS-CoV-2 infection risk among the INER-HCW. Finding: From March 1st to October 1st, 2020, 71.5% of INER-HCWs were tested for SARS-CoV-2 infection, and 77% of them were frontline workers. Among the tested INER-HCWs, 10.4% were positive for SARS-CoV-2 infection. Nonetheless, nosocomial infection represented only 3.8% of the cases and the mortality was null. 53% of INER-HCWs positive to SARS-CoV-2 had a negative test 42-56 days post-diagnosis and were returned to service. Finally, although a change in the PPE implemented on May 11th, 2020, the incidence of SARS-CoV-2 infection was not affected. Conclusion: INER has a lower incidence of HCWs infected with SARS-CoV-2 as compared to the mean of the national report. The implementation of the INER-POL-TRAB-COVID19 program is efficient to decrease the risk of infection among the HCWs. Our findings suggest that the implementation of a similar program at a national level can be helpful to provide a safe environment to HCWs and to prevent the collapse of health institutions.